Pengaruh Peran Ganda Perempuan dan Ujrah Pekerja terhadap Kemandirian Ekonomi Keluarga: (Studi pada Sistem Upah di Kelurahan Wirolegi, Jember) - Miftakhul Jannah; Ach. Faqih Supandi; Siti Hidayah (Yayasan Dharma Lentera Khatulistiwa (MALEWA), 2025)
This study aims to examine the influence of dual roles and ujrah on family economic independence in RW 11, Wirolegi Village, Jember. This study uses descriptive quantitative research with questionnaires as a data collection technique. Statistically-based data analysis intended to test hypotheses. In this study, the population used is the female community in RW 11, Wirolegi Village, Jember which totals 130 people. Perposive sampling is used as a data collection technique because the sample has certain criteria so that the population does not have the same opportunity to be used as a research sample. The sample size was determined using the slovin formula with a margin of error of 5% so that a figure of 98 people was obtained. In carrying out the data processing process using the spss program, the researcher used multiple linear regression analysis. From the results of data analysis, it can be found that the variable of women's dual role (X1) has an effect on family economic independence (Y). The ujrah variable (X2) has an effect on the economic independence of the family (Y). Meanwhile, simultaneously the dual role of women (X1) and ujrah (X2) has a positive and significant effect on family economic independence (Y).